3D site surveyor for 360° wireless motion tracking. (8th March 2010) - Hoorn, Johan F.; Otte, Marco
We developed a lightweight, wireless and most affordable three-dimensional tracking system, called 3D site surveyor, which allows versatile, hands-free and easy-to-use human?computer interaction, combining off-the-shelf hardware with custom-made software. We based this system on the Nintendo Wii remote controller hardware. 3D site surveyor is able to detect movement of a user in three dimensions (x, y and z-axis), including rotation in the xy-plane (yaw). We will argue that, within the limits of the system, it is theoretically possible to also measure pitch and roll, making the system capable of detecting 6DoF. The system can be applied to, for example, gaming, virtual reality, ambient-assisted living and academic research (e.g., human motion, perception and attention).